Chronic Hyperglycemia Drives Functional Impairment of Lymphocytes in Diabetic INSC94Y Transgenic Pigs - Giese, Isabella-Maria; Schilloks, Marie-Christin; Degroote, Roxane L.; Weigand, Maria; Renner, Simone; Wolf, Eckhard; Hauck, Stefanie M.; Deeg, Cornelia A. (Frontiers in Immunology, 2021)
People with diabetes mellitus have an increased risk for infections, however, there is still a critical gap in precise knowledge about altered immune mechanisms in this disease. Since diabetic INSC94Y transgenic pigs exhibit elevated blood glucose and a stable diabetic phenotype soon after birth, they provide a favourable model to explore functional alterations of immune cells in an early stage of diabetes mellitus in vivo. Hence, we investigated peripheral blood mononuclear cells (PBMC) of these diabetic pigs compared to non-transgenic wild-type littermates. We found a 5-fold decreased proliferative response of T cells in INSC94Y tg pigs to polyclonal T cell mitogen phytohaemagglutinin (PHA). Using label-free LC-MS/MS, a total of 3,487 proteins were quantified, and distinct changes in protein abundances in CD4+ T cells of early-stage diabetic pigs were detectable. Additionally, we found significant increases in mitochondrial oxygen consumption rate (OCR) and higher basal glycolytic activity in PBMC of diabetic INSC94Y tg pigs, indicating an altered metabolic immune cell phenotype in diabetics. Thus, our study provides new insights into molecular mechanisms of dysregulated immune cells triggered by permanent hyperglycaemia.